同向双螺杆挤出植物蛋白肉过程特性研究Characteristic of co-rotating twin-screw extrusion process for plant-based protein meat - 同向双螺杆挤出植物蛋白肉过程特性研究Characteristic of co-rotating twin-screw extrusion process for plant-based protein meat (Zhongguo youzhi)
旨在采用湿法挤压组织化技术生产植物蛋白肉制品,以缓解动物蛋白的供应压力和保证人体需要的蛋白质来源。基于同向双螺杆挤压机制备高质量拉丝蛋白，测量了植物蛋白肉物料的流变特性，建立模型并采用ANSYS Fluent对挤压机内流场进行全过程数值模拟，并验证数值模拟的可靠性，以及分析了挤出过程中流道内压强、速度、温度、剪切速率和剪切应力等关键参数的变化规律。结果表明：挤压机出口流量、螺杆扭矩和机头压强都随着螺杆转速的增加而增大，试验值与模拟值相对误差较小，验证了数值模拟的有效性，但高螺杆转速下过高的剪切应力会降低植物蛋白肉成型质量，其中螺杆转速为290 r/min时产品品质最佳；在螺杆转速290 r/min条件下，通过螺杆元件的排布和机筒壁面温度的控制，螺杆段流道的压强逐渐波动上升；物料温度随着壁面温度先升高后降低，靠近机筒的物料升温和降温都要更快，导致一定程度的壁面速度滑移；物料达到相分离临界温度的停留时间是螺杆转速的幂律函数，由此可确定双螺杆的适宜转速，以保证充分熟化和拉丝质量的工艺要求；剪切速率随螺杆转速的增加而增大，在啮合块处达到最大值；剪切应力在螺杆间隙处达到最大值。综上，可以通过数值模拟的方法指导植物蛋白肉的实际生产。 The purpose is to produce plant-based protein meat products by using wet extrusion texturing technology, to alleviate the supply pressure of animal protein and to ensure the protein source for daily life needs. High-quality pultruded proteins can be prepared using a co-rotating twin-screw extruder. The rheological properties of the plant-based protein meat were measured, and a model was developed for full-scale numerical simulation of the flow field in the extruder using ANSYS Fluent. The reliability of the numerical simulation was verified by comparing it with the experimental data. The changes of key parameters such as pressure, velocity, temperature, shear rate and shear stress in the flow channel during the extrusion process were analyzed. The results showed that the outlet flow, screw torque and head pressure increased with the increase of rotating speeds, and the relative error between experimental and simulated values was lower, which verified the validity of numerical simulation. However, the higher shear stress at high rotating speed reduced the plant-based protein meat′s molding quality. Among them, the product quality was the best when the rotating speed was 290 r/min. With the combined effect of screw elements design and wall temperature regulation at this rotating speed(290 r/min), the pressure of the flow channel in the screw section fluctuated and rose, and the material temperature first rose and then decreased with the wall temperature. Material closer to the barrel heated up and cooled down more quickly, resulting in wall velocity slip. The residence time for the material to reach the critical temperature for phase separation was a power law function of the rotating speed, by which the suitable rotating speed of the twin screw could be determined to ensure that the process requirements of full maturation and pultruding quality. The shear rate increased with the increase of screw rotating speed and reached its maximum at the kneading block. The shear stress reached its maximum value at the screw clearance. In conclusion, numerical simulation can be used to guide the actual production of plant-based protein meat.